1996
DOI: 10.1002/bjs.1800830117
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal angle enhances faecal continence

Abstract: This study was performed with an in vitro model to assess the relative importance of sphincter pressure and anorectal angulation in maintaining faecal continence. Water and semisolid material were infused separately into porcine intestine compressed by an inflatable cuff until leakage was observed. Angulation of the bowel with respect to the cuff was 180 degrees and then 90 degrees. With water, holdback pressure was independent of angulation. In contrast, when semisolid material was used, angling the bowel to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The puborectalis muscle contracts both in response to an increase in intra-abdominal pressure and in response to rectal filling (16). This apparent discrepancy may be due to the nature of the stool, since Hajivassiliou et al (22) have shown that the anorectal angle has a greater role in the maintenance of semisolid than liquid stool continence. There are conflicting data with regard to the importance of the anorectal angle in the clinical maintenance of continence.…”
Section: Maintenance Of Anorectal Anglementioning
confidence: 99%
“…The puborectalis muscle contracts both in response to an increase in intra-abdominal pressure and in response to rectal filling (16). This apparent discrepancy may be due to the nature of the stool, since Hajivassiliou et al (22) have shown that the anorectal angle has a greater role in the maintenance of semisolid than liquid stool continence. There are conflicting data with regard to the importance of the anorectal angle in the clinical maintenance of continence.…”
Section: Maintenance Of Anorectal Anglementioning
confidence: 99%
“…It is interesting, given the effect of puborectalis on anorectal angle, that the latter was not significant on univariate analysis ( P = 0.08), considering that there is evidence for its role in affecting continence [20]. It is perhaps more important to focus on the reduction in anorectal angle when the pelvic floor contracts as opposed to the normal resting angles observed in this study.…”
Section: Discussionmentioning
confidence: 81%
“…Notably, in vitro studies have shown that increasing ARA reduces the occlusion pressure required to hold back solids and semi-solids [22,23]. Similarly, another study reported increased retention of semisolid material when increasing ARA in an ex vivo porcine rectum, but no effect for water [23].…”
Section: Figure 1 Anatomy Of the Anorectum Components Which Are Modementioning
confidence: 97%
“…Notably, in vitro studies have shown that increasing ARA reduces the occlusion pressure required to hold back solids and semi-solids [22,23]. Similarly, another study reported increased retention of semisolid material when increasing ARA in an ex vivo porcine rectum, but no effect for water [23]. The question of whether the ARA or sphincter occlusion pressure is a greater contributor to continence remains unanswered, despite previous studies comparing the two [24,25].…”
Section: Figure 1 Anatomy Of the Anorectum Components Which Are Modementioning
confidence: 99%